Real Incentive Effects of Soft Information - Christensen, Peter O.; Frimor, Hans; Şabac, Florin (Contemporary Accounting Research, 2020)
ABSTRACT Both soft, noncontractible, and hard, contractible, information are informative about managerial ability and future firm performance. If a manager's future compensation depends on expectations of ability or future performance, then the manager has implicit incentives to affect the information. We examine the real incentive effects of soft information in a dynamic agency with limited commitment. When long‐term contracts are renegotiated, the rewards for future performance inherent in long‐term contracts allow the principal partial control over the implicit incentives. This is because the soft information affects the basis for contract renegotiation. With short‐term contracts, the principal has no control over the basis for contract negotiation, and thus long‐term contracts generally dominate short‐term contracts. With long‐term contracts, the principal's control over implicit incentives is characterized in terms of effective contracting on an implicit aggregation of the soft information that arises from predicting (forming expectations of) future performance. We provide sufficient conditions for soft information to have no real incentive effects. In general, implicit incentives not controllable by the principal include fixed effects, such as career concerns driven by labor markets external to the agency. When controllable incentives span the fixed effects of career concerns, the latter have no real effects with regard to total managerial incentives—they would optimally be the same with or without career concerns. Our analysis suggests empirical tests for estimating career concerns that should explicitly incorporate noncontractible information.